Care to pregnant women in primary care: report of activities in supervised training - Barreto, Mayckel da Silva; Mathias, Thais Aidar de Freitas (Rev Rene, 2013)
This is an experience report that describes an academic activity during Interdisciplinary In-training course, which is part of curricular program of the 4th year of the Nursing undergraduate course at a public university of the Paraná Northwest. As evaluation of the internship was elaborated an Action Plan based on the Altadir Method of Popular Planning, about prenatal care, focusing on the most common pregnancy complications. After researching the literature, observations during the internship, study in documents and reports of the health team, revealed was that anemia, followed by urinary complications, gastric and gynecological were pregnancy complications more frequent at the health unit. As a result of acquired knowledge together, several actions were undertaken, with professionals and pregnant women. The activities evidenced the relevance of Interdisciplinary In-training as an agent of the competences consolidation and technical abilities, providing the academic identify problems, develop intervention strategies and operational demands of the action. DOI: https://doi.org/10.15253/2175-6783.20130003000020